2018
DOI: 10.1021/acs.jpcc.8b05483
|View full text |Cite
|
Sign up to set email alerts
|

Mg–C Interaction Induced Hydrogen Uptake and Enhanced Hydrogen Release Kinetics in MgH2-rGO Nanocomposites

Abstract: Hydrogen uptake at 250 °C, P H2 > 15 bar and release at 320, 350 °C by MgH2 mixed with 10 wt % rGO alleviates the incubation period (slow kinetics) encountered during hydrogen release by pure MgH2. Ball milling establishes Mg–C interactions (∼283 eV) in these nanocomposites through electron-transfer from Mg to π* of C and weakens the C–C π bond. These Mg–C interactions persist in the nanocomposites upon subsequent hydrogen uptake and release. These interactions change the hybridization of C from sp2 to sp3, ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 65 publications
(144 reference statements)
1
25
0
Order By: Relevance
“…Any local changes in the chemical environment can cause deviation from these electronegativity values. In our earlier work, we demonstrated that the Mg-C interaction causes an increase of charge on carbon atoms leading to a change of hybridization in C from sp 2 to sp 3 , resulting in the C-H bond aiding H-uptake 18 .…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Any local changes in the chemical environment can cause deviation from these electronegativity values. In our earlier work, we demonstrated that the Mg-C interaction causes an increase of charge on carbon atoms leading to a change of hybridization in C from sp 2 to sp 3 , resulting in the C-H bond aiding H-uptake 18 .…”
Section: Discussionmentioning
confidence: 96%
“…The experimental data obtained from XPS were deconvoluted using Gaussian pro le to estimate the atomic interactions 27 . In C-1s spectra, the peaks at the binding energies ~283.2 eV, 283.3-283.9 eV, ~284.6 eV, ~285.7 eV, ~286.6 eV, and ~290 eV correspond to Mg-C 18 , B-C 28,29 , C-C sp 2 , C-OH, C-O-C 30,31 and C-2p π→π* transition 9,32 , respectively. The alcohol (-OH) and epoxy (C-O-C) functional groups arise during the synthesis of erGO (C-1s spectrum of erGO, Supplementary Fig.…”
Section: Chemical Interactionsmentioning
confidence: 99%
See 2 more Smart Citations
“…in the crystalline hydrogen-hosts upon H-uptake; this further renders (ii) the investigation of various atomic interactions among the components difficult; (iii) such uncertainties in structural investigations can lead to erroneous estimation of enthalpy and entropy changes. This is particularly true in the case of composite systems such as Mg(H 2 )-B-rGO, where both Mg and C (from rGO) can, synergistically, form bonds with H 9 , 18 . Our earlier study on H-uptake and release by Mg-rGO demonstrates that along with Mg, C also forms bond with H due to charge (electron) transfer from Mg to C 18 .…”
Section: Introductionmentioning
confidence: 99%